Analisis Pengembangan Model Supervisi Pendidikan Di Pondok Pesantren Darel Azhar Rangkasbitung - Soleh, Moh.; Bachtiar, Machdum; Saad, Suadi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
The Darel Azhar Rangkasbitung Islamic Boarding School as an Islamic educational institution has a central role in shaping the character and knowledge of the students. This research aims to analyze the development of the educational supervision model implemented at the Darel Azhar Rangkasbitung Islamic Boarding School. Using qualitative research methods and a descriptive study approach, this research describes the supervision model being implemented, evaluates the effectiveness of the model, and identifies challenges and development strategies being implemented. The research results show that the Darel Azhar Rangkasbitung Islamic Boarding School implements a supervision model that focuses on aspects of Islamic education, character and science. Evaluation of the effectiveness of the supervision model identified advantages in improving the quality of education, but also highlighted several weaknesses that need attention. Challenges in developing supervision models involve limited resources and contextual factors. However, this Islamic boarding school has implemented various strategies to increase the effectiveness of its supervision model with the Direct and Continue supervision model.. The implications of the results of this research provide contributions for managers and practitioners in Islamic boarding schools as well as parties interested in developing Islamic education supervision models